Cape Verde : Second Review Under the Poverty Reduction and Growth Facility Arrangement. (IMF Staff Country Reports; Country Report, 2003)
Executive Directors commend the government for their continued commitment to restore macroeconomic stability and implement structural reforms to establish the foundation for high rates of economic growth and poverty reduction. The medium-term economic strategy is appropriate. The risks to the program are acceptable. The implementation of the value-added tax and the new customs tariffs have been subject to repeated delays. The measures to stem the losses of wholly state-owned public enterprises have been commended. Cape Verde's statistical system remains weak, but is improving.